Set Size of Information in Long-Term Memory Similarly Modulates Retrieval Dynamics in Young and Older Adults - Peters, Jan O.; Steiger, Tineke K.; Sobczak, Alexandra; Bunzeck, Nico (Frontiers in Psychology, 2022)
Our ability to rapidly distinguish new from already stored (old) information is important for behavior and decision-making, but the underlying processes remain unclear. Here, we tested the hypothesis that contextual cues lead to a pre-selection of information and, therefore, faster recognition. Specifically, on the basis of previous modeling work, we hypothesized that recognition time depends on the amount of relevant content stored in long-term memory, i.e. set size, and we explored possible age-related changes of this relationship in older humans. In our paradigm, subjects learned by heart four different word lists (24, 48, 72, 96 words) written in different colors (green, red, orange, blue). On the day of testing, a color cue (e.g. green) indicated with a probability of 50% that a subsequent word might be from the corresponding list or from a list of new words. The old/new status of the word had to be distinguished via button press. As a main finding, we can show in a sample of n=49 subjects, including 26 younger and 23 older humans, that response times increased linearly and logarithmically as a function of set size in both age groups. Conversely, corrected hit rates decreased as a function of set size with no statistically significant differences between both age groups. As such, our findings provide empirical evidence that contextual information can lead to a preselection of relevant information stored in long-term memory to promote efficient recognition, possibly by cyclical top-down and bottom-up processing.